POTENSI BERBAGAI JENIS VEGETASI SEBAGAI HIJAUAN PAKAN TERNAK DI PADANG PENGGEMBALAAN KAMPUNG SOTA, KABUPATEN MERAUKE - Irine Ike Praptiwi; Diana Sri Susanti; Aloysia Tenny Damayanti; Yosefina Mangera; Nafiatul Umami (Universitas Musamus, Merauke, Papua, 2017)
Forage availability become a major issue in the provision of feed, especially during the dry season. The purpose of this study is to identify the type of vegetation in the grazing fields that have been used by people in the village of Sota. The data were taken from the area around the used rice field in the village of Sota. The forage classified as grass, legume and forbs. The method applied in the research by observing the botanical composition there at several observation points. The forage was taken as the sample, then calculated the production and analyzed the content of dry material. The results showed that the vegetation found in the used rice fields in the village of Sota, there are 33 vegetation, consisting of legume, grass and forbs 3, 61 and 36%. Vegetation types most commonly found are Fimbristylis genus, Paspalum and species of Calopogonium mucunoides the SDR value of 9.88; 9.3 and 9.74%. Composite dry matter production of 757.62 kg /ha with measuring capacity 1,68 AU